2009
DOI: 10.1016/j.bpc.2009.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling of amphotericin B–ergosterol primary complex in water II

Abstract: The work presented is a part of our continual study on the behavior of the polyene macrolide antibiotic amphotericin B (AmB) complexes with sterols on the molecular level. In contrast to the previously researched AmB-ergosterol binary complex, the AmB-ergosterol-AmB aggregates simulated of 2:1 stoichiometry retain significantly higher stability and relatively rigid, "sandwich" geometry. Van der Waals forces with a considerable share of the electrostatic interactions are responsible for such behavior. System of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 35 publications
3
30
1
Order By: Relevance
“…Other factors should be taken into account when discussing the phenomenon of AmB -sterol differential affinity in the complex formation. The reported results of simulations of isolated sterol molecules confirm our findings from simulations of AmBsterol complexes [19,20]. Molecules of ergosterol or cholesterol (unpublished results) and antibiotic may fit their shapes to each other to some extent in order to assure the largest intermolecular contact.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Other factors should be taken into account when discussing the phenomenon of AmB -sterol differential affinity in the complex formation. The reported results of simulations of isolated sterol molecules confirm our findings from simulations of AmBsterol complexes [19,20]. Molecules of ergosterol or cholesterol (unpublished results) and antibiotic may fit their shapes to each other to some extent in order to assure the largest intermolecular contact.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noted that during our simulations all the sterols studied existed predominantly in the conformation Àsc/ap. According to the present model of the AmB-sterol complex and our previous studies [19,20], also other conformations, in which the side chain is coplanar to the ring system (+sc/Àsc and Àsc/Àsc), could form a stable complex. Thus, for all the sterols studied conformations that are able to form the complex have been observed during more than 57% of the simulation time.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The results showed that the MIC of IVS320 against C. albicans ATCC 36232 did not change in the presence of different concentrations (200 to 800 μg/mL) of exogenous ergosterol (Figure 2), suggesting that IVS320 does not act by interacting with ergosterol. In contrast, there was a 4× MIC increase with amphotericin B, which is known to have a strong affinity for ergosterol and served as the positive control in this assay [14]. …”
Section: Resultsmentioning
confidence: 99%
“…In the presence of cholesterol, the MIC value of citral increased to 1024 µg/mL (two-fold), and the MIC of amphotericin B increased four times, as shown in Tables 3 and 4. Amphotericin B has a strong affinity for ergosterol, while it has a weak affinity for cholesterol, and this is due to the double bond in the ergosterol molecule increasing the stability of interaction between amphotericin B and ergosterol (Baran et al, 2009).…”
Section: Discussionmentioning
confidence: 99%